Visibilidad internacional de las Revistas Españolas de Historia Moderna - Malalaña Ureña, Antonio (Cuadernos de Historia Moderna, 2007)
Spanish history journals, the same as other publications, are being submitted from different methodological criteria to quality control. One of these criteria is to try to establish the levels of international visibility of each of them. In the following work a small group of Spanish Modern History journals has been analised.